Induced maturation and ovulation in Heteropneustes fossilis by using LHRHa, pimozide and ovaprim for production of quality eggs and larvae - Nayak, P K; Mishra, T K; Singh, B N; Pandey, A K; Das, R C (Indian Journal of Fisheries, 2011)
In this study, the effect of luteinizing hormone-releasing hormone analogue(LHRHa), pimozide (PIM) and ovaprim on oocyte maturation, ovulation andspawning of Heteropneustes fossilis has been evaluated. Both LHRHa and pimozidewhen tested alone, failed to evoke any ovulation response, although both drugsresulted in the advancement of oocyte maturation in catfish as evidenced fromgerminal vesicle migration. On the other hand LHRHa + PIM (0.05 ug + 5 ug/g/body weight respectively) when administered in combination intraperitoneally,caused high rate of ovulation and produced an average of 10±2.3 g eggs with highrate of hatching (93.5 ± 1.42%) and high yield of normal larvae (87.3±3.3 %). Asingle dose (0.6 - 0.8 ml/kg) of ovaprim injected intramuscularly resulted in anaverage production of 13.75 ±2.9 g eggs having 96.3± 1.7% hatchability and yielded92.5 ± 1.5% of normal larvae. The latency period (interval between the time ofinjection and spawning) ranged between 15-18 hrs in LHRHa + PIM and 10-12hrs in ovaprim treated fish. The eggs produced after induced spawning wereviable and fertilized in vitro using homogenized testes and produced higher yieldof normal larvae, minimizing deformed and crawled larvae. This finding suggeststhe application of LHRHa + PIM and/or ovaprim for inducing ovulation and successfulbreeding, as a replacement to hypophysation and achieving quality eggand larval production for successful catfish cultivation in the country.